Resilience Theory, Information Behaviour and Social Support in Everyday Life - Hersberger, Julie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
LIS professionals may benefit from understanding resiliency theory in order to better serve users who have experienced stressful or adverse life events. This paper examines key theoretical concepts of stress, resilience, affect and cognition overlap and social support as key elements of coping or buffering the individual from negative outcomes. Les professionnels de la bibliothéconomie et des sciences de l’information tireraient profit d’une meilleure compréhension de la théorie de la résilience lors de la prestation de services aux usagers en situation de stress. Cette communication examine les concepts théoriques clé que sont le stress, la résilience, le chevauchement de l’affectif et du cognitif ainsi que le soutien social comme éléments de réponse et de défense aux situations négatives.